FANSUR SEBAGAI KOTA TUA ISLAM - E. Edwards McKinnon; Nurdin AR (Indonesian Journal of Islamic History and Culture, 2020)
Fansur is an ancient Islamic city in Nusantara (the Indonesian archipelago) which was very popular in the past. However, the specific location of the city is still being debated today. Generally, contemporary writers state that Fansur is located in Barus, one of the areas in Central Tapanuli, North Sumatra. This opinion has been challenged from several authoritative sources. To solve the above problems, this research was conducted through an archaeological approach and literature study. Based on archaeological evidence and written sources, Fansur City is located in Lhok Pancu or Lhok Lambaroneujid, one of the coastal areas to the west of the city of Banda Aceh, Aceh. This location fits perfectly with the character of the Fansur location mentioned in ancient records from the Middle East, China and Europe. Due to geological changes that have occurred frequently in the past in the Aceh region, most of the area has been lost and cannot be seen again. The remains of ancient ceramics, tombstones and ancient tomb complex (diway) are archaeological evidence to strengthen the argument that Fansur is an ancient Islamic port city located in the Aceh Besar region, not in Barus, Central Tapanuli.